Long-term outcome and cancer incidence after lower extremity bypass surgery in patients with critical limb threatening ischemia - Michailidis, Polykarpos; Epple, Jasmin; Böckler, Dittmar; Schmitz-Rixen, Thomas; Grundmann, Reinhart T. (Langenbeck's archives of surgery, 2023)
The influence of cancer development on long-term outcome after lower extremity bypass surgery in patients with critical limb threatening ischemia was investigated.
Gesehen am 18.01.2024